If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + y = 26 Solving 9x + y = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 9x + y + -1y = 26 + -1y Combine like terms: y + -1y = 0 9x + 0 = 26 + -1y 9x = 26 + -1y Divide each side by '9'. x = 2.888888889 + -0.1111111111y Simplifying x = 2.888888889 + -0.1111111111y
| 5n-8=-14+3n | | F(0)=6x-8 | | 3x+5=.50 | | x+6+x=134 | | 17c+15d-10c= | | 5(9x-8)= | | 4x+2=x-14 | | 156=4(6x-9) | | 4x+2=x+16 | | 6x+10=8+7x | | log(43-7x)=0 | | 6/-7=3/4 | | .17(q)+3.2=5.75 | | 20/1•4/1 | | H-(-12)=7 | | 5x-7=18x+3 | | x+10=24-5x | | (3x+2)+50=x | | 2s+10-7s-8+3s=2-2s | | (x+10)+4x=x | | -8(x+3)=-5(x+4) | | 180=85+(2x+25) | | 2x-2x=4x | | 2s+10-7s-8+3s= | | 2x-2x=ax | | (4x+1)+69=x | | (4x+3)+55=x | | w+3+w=1.70 | | (4x+2)+70=x | | (4x+1)+41=x | | 4r+.16=3.25 | | 3(5-x)=2x-10 |